Shared Prosperity : Links to Growth, Inequality and Inequality of Ppportunity - Narayan, Ambar (World Bank, Washington, DC, 2014)
Focusing on the welfare of the less well off as a measure of real societal progress is the fundamental principle underlying the WBG indicator of "shared prosperity", namely income growth of the bottom 40 percent in every country. This paper uses a database assembled by the World Bank Group to investigate some basic characteristics of shared prosperity, particularly its relationship with overall economic growth and inequality. Initial estimates using this dataset of 79 countries show that median income growth of the bottom 40 percent (circa 2005-2010) was 4.2 percent, a high number in comparison to the 3.1 percent per capita income growth of the overall population. In addition, the low and lower-middle income countries appear to be trailing the upper middle and high income countries in boosting shared prosperity. Establishing conceptual links between income growth of the bottom 40 percent, the overall growth rate and reviewing existing evidence on how these relate to inequality, the paper discusses two main ideas. First, shared prosperity is strongly correlated with overall prosperity implying that the whole host of policies that are important to generate and sustain growth remain relevant. Second, boosting shared prosperity will also require a concerted effort to strengthen the social contract, particularly in the area of promoting equality of opportunity. Growing evidence suggests that improving access for all and reducing inequality of opportunities -- particularly those related to human capital development of children -- are not only about "fairness" and building a "just society", but also about realizing a society's aspirations of economic prosperity.